Modeling of C stocks in the soil in the production systems of the Orinoquia region (Colombia) - Parra Silva, Amanda; Cely Reyes, Germán Eduardo; Pérez Fagua, Carmenza (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Soils can act as emitters or sinks of greenhouse gases, depending on soil management factors. The modeling of soil C stocks using the IPCC methodology allows the definition of changes in soil C stocks in productive systems in tropical systems. The IPCC methodology was applied at a Tier 2 level of detail using default values in different scenarios of soil management factors such as land use (polyculture and monoculture; short/long term), type of tillage (full, reduced and no tillage), input level of residues (high, medium and low), to estimate the final soil C stocks from the determination of reference C stocks, the rates of soil C losses and/or gains, and the emissions and/or absorptions of CO2 from the soil to the atmosphere in different productive systems of Orinoquia with 20-year projections, in order to propose mitigation strategies against global climate change.The results showed that the conversion of rice monoculture from Villavicencio to the rice monoculture system in rotation with corn and soybeans from Granada would increase the C stock by about 12.31 t ha-1 in 20 years, equivalent to 0.61 t ha-1 year-1, which would reduce emissions by 2.27 t CO2 eq ha-1 year-1. The change in land use from cocoa monoculture systems from Puerto López to cocoa agroforestry systems with Acacia mangium from Villavicencio and from improved pastures from Granada to silvopastoral systems of pastures improved with A. mangium from Puerto López would increase the soil C stocks of about 17.72 and 40.92 t ha-1 in 20 years, equivalent to 0.88 and 2.04 t ha-1 year-1 and emissions would be neutralized by about 3.25 and 7.48 t CO2 eq ha-1 year-1, respectively.Faced with soil sustainability strategies and climate change, agroforestry and/or silvopastoral systems, as well as rotational systems, showed a positive balance of C storage in the soil and a negative balance in atmospheric levels of greenhouse gases, which can contribute in part to mitigating the negative effects of climate change in the Orinoquia and the greenhouse gases generated in the country and/or the world.